Effects of bar-transgenic rice on the intestinal microflora of the mice (Mus musculus) - Liu, Jin; Huang, Yi; Sun, Yanbo; Yan, Hengmei (Scientific Research Publishing, 2012)
Microbial molecular ecology approaches were used to the effects of Bar-transgenic rice on Intestinal Micro-flora of the Mice (Mus musculus). Kunming mice (Mus musculus) of 100 SPF-grade (20 g ± 2 g), half of which were male and the other half female, were randomly divided into five groups with four replications per group and five mice per replication to assess the safety of Bar-transgenic rice. Five diets meetinging or exceeding the minimum nutrient requirement were fed for 180 days. After 90 days, parental generation (P) was bred to produce the first filial generation (F1). Each generation was fed for 180 days. On the 180th day, five mice from each group were randomly sampled, and their intestinal contents were collected for DNA isolation. The V3 region of the 16S rDNA was amplified by polymerase chain reaction (PCR) and analyzed via denaturing gradient gel electrophoresis (DGGE). The resulting PCR-DGGE band number (bacterial species) was counted, and the banding patterns were analyzed by calculating the Sorenson’s pairwise similarity coefficients (Cs), an index used to measure bacterial species found among all samples. The sequence analysis of bands was performed to identify the intestinal predominant microflora of the mice. The intergroup Cs values of the samples across all groups did not differ (P > 0.05) from each other. The effect of Bar-transgenic rice on the intestinal microflora of the mice was considered insignificant.
Keywords: Bar-Transgenic Rice; Mus musculus; Intestinal; Microflora; Denaturing Gradient Gel Electrophoresis